Síntese hidrotermal de materiais nanoestruturados derivados do óxido de nióbio e aplicação nas reações de Mannich - Pereira, Gabriela Alcoforado (2023)
Recent discoveries have revealed the remarkable versatility and applicability of materials derived from niobium pentoxide (Nb2O5) in several fields, such as catalysis, electrocatalysis and photocatalysis, among others. Therefore, the understanding and search for specific properties of Nb2O5 and its derivatives for each type of application has aroused interest. With regard to heterogeneous catalysis, for example, some properties are required, such as high surfaces area, presence of acidic sites, insolubility in the reaction medium and selectivity. Each material has its specific properties, however, these properties can be changed through heat treatments or the addition of other substances through a chemical process. When a material is obtained on a nanometric scale and some of its properties are altered in relation to the starting material, we have a nanostructured material. Currently, the synthesis of these materials can be carried out by different methodologies, such as the alkaline hydrothermal method, which has been highlighted for allowing the control of the size and shape of the particles. In this work, we report the synthesis of nanostructured materials derived from Nb2O5 using the alkaline hydrothermal method, and subsequent application of these materials in the synthesis of 2- [phenyl(phenylamino)methyl]cyclohexanone through the Mannich reaction. For the synthesis of materials, several reaction parameters were evaluated, including reaction time and temperature. By evaluating these parameters, it was possible to direct the size and shape of the nanostructures. At 140 ºC, 9 mol L-1 of NaOH and 24 hours of reaction, nanotubular structures (NtNb-24.1 and NtNb-24.2) were obtained with diameters ranging from 183.01 to 531.5 nm, with the presence of intermediate metastructures, and a band gap value of 5.65 eV. After 48 hours of reaction, microcubes (McNb) with diameters between 1.73 and 7.75 µm were obtained, with the orthorhombic phase present and band gap values of 5.71 eV. The morphology of microcubes with similar characteristics was also obtained at 160 ºC in 24 hours. The catalytic efficiency and selectivity of the synthesized materials were evaluated and compared with the catalytic efficiency of Nb2O5, titanium oxide (TiO2), titanium nanotube (NtTi) and the organocatalyst L-proline in the Mannich multicomponent reaction. Like the Nb2O5, TiO2, NtTi and L-proline catalysts, NtNb-24.2 was diastereoselective, preferentially leading to the formation of the anti-2- [phenyl(phenylamino)methyl]cyclohexanone isomer. When using the Nb2O5 microcube, the predominant compound formed was N-phenylcyclohexanimine. These results are promising and show the potential of these nanostructured materials as efficient and selective catalysts.